A Systematic Review of Web-Based Educational Interventions. (February 2015) - Fredericks, Suzanne; Martorella, Géraldine; Catallo, Cristina
A complement to in-hospital educational interventions is web-based patient education accessed during the home recovery period. While findings demonstrate the effectiveness of web-based patient education interventions on patient outcomes, they fall short of identifying the characteristics that are associated with desired outcomes. The purpose of this systematic review was to determine the characteristics of web-based patient education interventions that are associated with producing changes in self-care behaviors. A systematic review involving 19 studies was conducted to determine the most effective components of a web-based intervention. Findings suggest that the most effective form of web-based patient education is one that is interactive and allows patients to navigate the online system on their own. The findings from this systematic review allow for the design of a web-based educational intervention that will promote increased performance of self-care behaviors during the home recovery period.